Visual, cortical somatosensory and brainstem auditory evoked potentials following incidental irradiation of the rhombencephalon. - Nightingale, S (1984)
Visual, cortical somatosensory and brainstem auditory evoked potentials were recorded before incidental irradiation of the rhombencephalon and at 11 weeks and eight months after completion of treatment. No patient experienced neurological symptoms during this period. No consistent changes in evoked potentials were found. The failure to demonstrate subclinical radiation-induced demyelination suggests either that the syndrome of early-delayed radiation rhombencephalopathy occurs in an idiosyncratic manner, or that any subclinical lesions are not detectable by serial evoked potential recordings.